2013
DOI: 10.1099/vir.0.050526-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in haemagglutinin that affect receptor binding and pH stability increase replication of a PR8 influenza virus with H5 HA in the upper respiratory tract of ferrets and may contribute to transmissibility

Abstract: The H5N1 influenza A viruses have circulated widely in the avian population for 10 years with only sporadic infection of humans observed and no sustained human to human transmission. Vaccination against potential pandemic strains is one strategy in planning for future influenza pandemics; however, the success of live attenuated vaccines for H5N1 has been limited, due to poor replication in the human upper respiratory tract (URT). Mutations that increase the ability of H5N1 viruses to replicate in the URT will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 47 publications
3
61
0
Order By: Relevance
“…We speculate that the high pH optimum of HA-mediated fusion can be responsible for the pathogenicity of this virus. Dependence of replication efficiency and pathogenicity of influenza viruses on fusion pH was well documented previously (Brown et al, 2001;Hsu et al, 2006;Reed et al, 2010;Shelton et al, 2013).…”
Section: Discussionmentioning
confidence: 62%
“…We speculate that the high pH optimum of HA-mediated fusion can be responsible for the pathogenicity of this virus. Dependence of replication efficiency and pathogenicity of influenza viruses on fusion pH was well documented previously (Brown et al, 2001;Hsu et al, 2006;Reed et al, 2010;Shelton et al, 2013).…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, two independent studies showed that adaptation of H5 viruses to the upper respiratory tracts of ferrets and the acquisition of airborne transmissibility required a mutation that lowered the HA activation pH from 5.6 to 5.2-5.4 (7,8). In addition, α-2,6 sialic acid receptor specificity and efficient polymerase activity at 33°C (the temperature of mammalian upper airways) were also required (8,23,25). In contrast to the upper respiratory tract, in the lungs, a lower HA activation pH has been associated with reduced virus growth and reduced or delayed pathogenicity for H5N1 viruses (23,26).…”
Section: Discussionmentioning
confidence: 99%
“…A higher HA activation pH (5.6-6.0) enhances replication of HPAI viruses in the enteric and respiratory tracts of ducks and chickens by facilitating membrane fusion (20,22). Such facile activation of the HA protein leads to virion inactivation in mildly acidic pH environments, such as the mammalian upper respiratory tract (7,8,23,25). The airways of mammals are mildly acidic (pH 5.5-6.9) (27) and become more acidic (pH 5.2) during influenza virus infection (28).…”
Section: Discussionmentioning
confidence: 99%
“…Both a switch in receptor binding specificity to ␣2-6-linked SA and a lowered HA activation pH have been found to be essential for the heightened replicative ability in upper respiratory tract tissues and the aerosol transmissibility of H5N1 mutant viruses in ferrets (34,55,56). A few substitutions at the HA trimer interface and stem region have been identified to be responsible for the changes in the HA fusion threshold (34,55,56), though further study is required to identify the precise substi-tution(s) in the 2016 H7N2 virus compared with the sequence of other LPAI H7N2 viruses that may be present and might contribute to the reduced HA fusion threshold for NY/108 virus observed here. In addition to differences in activation pH, the presence of 702Arg in PB2 in both human and feline H7N2 isolates, in contrast to the 702Lys present in NY/107 virus, represents an additional marker for mammalian host adaptation (57) and was found in only a subset of H7N2 avian viruses isolated from 1999 to 2002.…”
Section: Discussionmentioning
confidence: 99%